Analysis of Factors Affecting Sharia Capital Market Performance in Indonesia - Srie Nuning Mulatsih; Aisyah Ratnasari; Dadang Saepuloh (Review of Islamic Economics and Finance (RIEF), 2019)
This research is a quantitative descriptive study that aims to measure the company's Infrastructure, Utilities, and Transportation sectors using Economic Value Added (EVA) and see whether there is value creation for the company after EVA calculation. The population in this study is an infrastructure company listed on ISSI. In contrast, the sample used in this study is 12 infrastructure sector companies listed on the ISSI during 2015-2017, respectively. The type of data used is the type of secondary data that the author gets through the financial statements of each company from 2015-2017 published on the IDX website. The performance measurement method used in this study is the EVA method, which consists of 3 components of calculation: Net Operating After-Tax Profit, Weighted Average Cost of Capital, and Invested Capital. The results of this study indicate that the performance of infrastructure sector companies listed on ISSI in the period 2015 to 2017 shows the results of EVA valuations are diverse, namely: Companies that have positive, fixed, negative EVA. PT Cardig Aero Service and TLKM succeeded in showing good EVA growth from 2015-2017. As evidenced by 2017, EVA has continued to increase in 3 consecutive years, having positive EVA values